Ligand-free copper-catalyzed O-arylation of arenesulfonamides with phenols: An unusual approach to biaryl ether synthesis. Issue 6 (19th March 2019) - Chen, Junmin; Wang, Junmin; Chen, Xida; Huang, Yuming; Shouzhi, Pu
Abstract: An unprecedented ligand-free copper-catalyzed O -arylation of arenesulfonamides with phenols has been developed. Thus, a range of unsysmmetric biaryl ethers were synthesized in excellent yields. The reaction occurs efficiently with excellent regioselectivity through the cleavage of Cary -S bond and with a good tolerance of functional groups on the phenyl ring of phenols. The reaction is appreciated for its readily accessible substrates, mild conditions, and simple operation under air. Graphical Abstract: